Electrochemically Stable Cobalt–Zinc Mixed Oxide/Hydroxide Hierarchical Porous Film Electrode for High-Performance Asymmetric Supercapacitor - Yang, Hanbin (Nanomaterials (Basel), 2019)
Construction of electrochemically stable positive materials is still a key challenge to accomplish high rate performance and long cycling life of asymmetric supercapacitors (ASCs). Herein, a novel cobalt–zinc mixed oxide/hydroxide (CoZn-MOH) hierarchical porous film electrode was facilely fabricated based on a cobalt–zinc-based metal–organic framework for excellent utilization in ASC. The as-constructed hierarchical porous film supported on conductive Ni foam possesses a rough surface and abundant macropores and mesopores, which allow fast electron transport, better exposure of electrochemically active sites, and facile electrolyte access and ion diffusion. Owing to these structural merits in collaboration, the CoZn-MOH electrode prepared with a zinc feeding ratio up to 45% at 110 min of heating time (CoZn-MOH-45-110) exhibited a high specific capacitance of 380.4 F·g(−1), remarkable rate capability (83.6% retention after 20-fold current increase), and outstanding cycling performances (96.5% retention after 10,000 cycles), which exceed the performances of similar active electrodes. Moreover, an ASC based on this CoZn-MOH-45-110 electrode exhibited a high specific capacitance of 158.8 F·g(−1), an impressive energy density of 45.8 Wh·kg(−1), superior rate capability (83.1% retention after 50-fold current increase), and satisfactory cycling stability (87.9% capacitance retention after 12,000 cycles).